Masjid Al-Osmani : Telaah Sejarah Sosial Keaagamaan - Abdul Gani Jamora Nasution; Lisa Sabina; Liza Umami; Rahmanita Minta Ito Pulungan; Shakira Fadla Nasution (Prodi Perpustakaan dan Sains Informasi, 2022)
This research aims to make the surrounding community pay more attention to one of the historical relics or mosques in the city of Medan. This study uses the historical research method, which is a method used in collecting historical sources (heuristics). The sample obtained using the interview technique was 5 people in the community around the Osmani mosque. Al Osmani Grand Mosque is located in the area of ​​Jalan Yos Sudarso KM. Pekan Labuhan Village, Medan Labuhan District, Medan, founded by Sultan Deli VII Osman Perkasa Alam, is not only a building that functions as a place of worship. But basically the Al-Osmani Grand Mosque is a cultural blend of Chinese, Middle Eastern, Indian, Spanish and local ethnicities in the city of Medan, namely the Malay ethnicity